2020
DOI: 10.7717/peerj.9629
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis is normal in Tex33 knockout mice

Abstract: Testis expressed gene 33 (Tex33) is a recently reported testis-specific gene and it is evolutionarily conserved in vertebrates. The Tex33 expression is found in cytoplasm of round spermatids in Mus musculus. However, the in vivo function of Tex33 remains unknown. In this study, we made a 62bp in frame deletion on Exon2 of Tex33 gene by CRISPR/Cas9 in C57B/L6 mouse, which cause frame shift mutation of Tex33 gene. Tex33-/-adult male were fertile, and there is no significant change on litter size compared with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…The basic common function of all WD40-repeat proteins is to coordinate the assembly of multi-protein complex, where the repeating units act as a rigid scaffolds for protein interactions 22 . The complex structure of sperm flagella contained a series of WD40-domain-containing proteins 1 , 23 . These proteins including CFAP43 (also known as WDR96 , MIM: 617558), CFAP44 (also known as WDR52 , MIM: 617559) and WDR66 (MIM: 618146) are associated with MMAF and their bi-allelic variants can reduce sperm motility and cause male infertility 24 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic common function of all WD40-repeat proteins is to coordinate the assembly of multi-protein complex, where the repeating units act as a rigid scaffolds for protein interactions 22 . The complex structure of sperm flagella contained a series of WD40-domain-containing proteins 1 , 23 . These proteins including CFAP43 (also known as WDR96 , MIM: 617558), CFAP44 (also known as WDR52 , MIM: 617559) and WDR66 (MIM: 618146) are associated with MMAF and their bi-allelic variants can reduce sperm motility and cause male infertility 24 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Infertility is a global human health concern and affects approximately 8%–12% of couples around the world 1 , 2 . Male infertility, which accounts for half of all infertility cases, is generally manifested by reduced sperm count (oligozoospermia and azoospermia), reduced sperm motility (asthenozoospermia), or increased percentage of abnormal sperm morphology (teratozoospermia).…”
Section: Introductionmentioning
confidence: 99%
“…Tex33 expression is testis-specific; the encoded protein is found in the cytoplasm of round spermatids but much less in elongated spermatids [ 48 ]. Given that spermatogenesis is normal in male tex33 -null mice, Tex33 might not be essential [ 49 ].…”
Section: Tex Gene Expression and Function In The Mousementioning
confidence: 99%
“…Sperm physiology and motility are abnormal, which impair sperm migration into the oviduct and hinder the acrosome reaction. TEX101 is therefore essential for male fertility; it has been suggested that TEX101 operates as a cell surface chaperone involved in the maturation of proteins required for sperm migration and sperm-oocyte interaction (such as Adam3) [49][50][51][52][54][55][56][57].…”
Section: Tex101mentioning
confidence: 99%
“…For example: T-complex-associated-testis-expressed 1 (TCTE1) is an important axonemal protein that is required for sperm motility (5); F-box protein 47 (FBXO47) is localized specifically in spermatocytes and directs integration between the telomere and inner nuclear envelope during meiotic progression (6); MRN complex interacting protein (MRNIP) is a MRN-interacting protein essential for chromosome synapsis and meiotic homologous recombination (7). On the other hand, we have also shown that several genes [Retinoic acid induced 14 (Rai14), testis expressed 33 (Tex33), Fibronectin type 3 and ankyrin repeat domains 1 (Fank1), and Eukaryotic elongation factor-2 kinase (Eef2k)], previously postulated as crucial factors for spermatogenesis, are dispensable for spermatogenesis and male fertility (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%